DC/AC electrical fundamentals - Patrick, Dale R.; Fardo, Stephen W.; Richardson, Ray E., 1961-; Chandra, Vigyan, 1968- (River Publishers series in electronic materials and devices., 2022)
This book explores many essential topics in a basic and easy-to-understand manner. This book, and the accompanying Electronic Devices and Circuit Fundamentals, have been modified with significant updates in content. The books are developed using a classic textbook ⁰́₃ Electricity and Electronics: A Survey (5th Edition) ⁰́₃ as a framework. Both new books have been structured using a similar sequence and organization as previous editions. The previous edition of Electricity and Electronics: A Survey contained 18 chapters, 8 in the Electricity section and 10 in the Electronics section. This book has been expanded to include 19 chapters, further simplifying content, and providing a more comprehensive coverage of the content. The content has been continually updated and revised through new editions and by reviewers over the years. Additional quality checks to ensure technical accuracy, clarity and coverage of content have always been an area of focus. Each edition of the text has been improved through the following features: 1. Improved and updated text content. 2. Improved usage of illustrations and photos. 3. Use of color to add emphasis and clarify content.